Histopathological Changes in Third-Instar and Adult Anastrepha ludens (Diptera: Tephritidae) After in vitro Heat Treatment. Issue 1 (22nd March 2015) - Caro-Corrales, Lorena; Caro-Corrales, Jose; Valdez-Ortiz, Angel; Lopez-Valenzuela, Jose; Lopez-Moreno, Hector; Coronado-Velazquez, Daniel; Hernandez-Ortiz, Emilio; Rendon-Maldonado, Jose
Abstract : The Mexican fruit fly, Anastrepha ludens Loew (Diptera: Tephritidae), is one of the most harmful pests of mango causing direct damage by oviposition on the fruit pulp. Mango for export is subjected to hydrothermal treatment as a quarantine method for the control of this pest, but exposure to heat for long periods of time reduces considerably the quality and shelf-life of treated fruit. The aim of this work was to study morphological changes of third-instar larvae and adults of A. ludens after in vitro exposure to high temperature at sublethal times. A heating block system was used to expose larvae at 46.1°C for 19.6 and 12.9 min, producing 94.6 and 70% mortality, respectively. Treated larvae were processed for optical microscopy. A fraction of surviving treated larvae was separated into containers with artificial diet to allow development into adults. Adult sexual organs were dissected and processed for transmission electron microscopy analysis. Results showed that 94.6% of the treated larvae died at 46.1°C for 19.6 min and none of the surviving larvae eclosed to adulthood, as they developed as malformed puparia. For the in vitro treatment at 46.1°C during 12.9 min, 70% of the treated larvae died and only 3.75% reached the adult stage, but ultrastructural damage in the male testes and in the female ovaries was observed. Additionally, 11.1% of the adult flies from the in vitro treatment also showed wing malformation and were incapable of flying. The analysis showed that surviving flies were unable to reproduce.